Optimizing AI-Driven Reservation Systems for Travel Agencies Using Human-Centered Design Principles to Improve Efficiency and Accuracy - Islamiyah, Mufidatul; Sunarto, Billy Tian (LPPM STIKI Malang, 2024)
Traditional land-based travel agencies offering services like taxis, cars, minibusses, and buses face inefficiencies due to manual reservation processes. These methods often lead to errors and delays, resulting in customer dissatisfaction. This paper presents the development of a web-based reservation system designed using Human-Centered Design (HCD) methodology to reduce errors, accelerate processes, and enhance customer experience. AI is integrated to automate order validation and confirmations, while ensuring staff maintain control over the final steps. Surveys and interviews with stakeholders, including business owners and customers, will be conducted to refine the system based on real-world insights.